2008
DOI: 10.1007/s11630-008-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of partially shrouded impeller in a small centrifugal compressor

Abstract: Numerical analysis is conducted for the 3-dimensional impeller and vaneless diffuser of a small centrifugal compressor. The influence of impeller tip clearance on the flow field of the impeller is investigated. Detailed investigation on the leaking flow across the tip clearance of the impeller shows that the leaking flow rate is higher near the exit of the impeller than that near the inlet of the impeller. Based on this phenomenon, a new partially shrouded impeller is designed. The impeller is shrouded near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Ishida et al [4] had tested centrifugal blowers with different shapes (square, round, and E-type, i.e., with an extension on the pressure surface side) and found that E-type tip provided improved performance. The concept of partial shrouded rotor in a small high-speed high-pressure ratio centrifugal compressor was computationally investigated by Tang et al [5]. They found that the leakage flow was reduced in the partially shrouded rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Ishida et al [4] had tested centrifugal blowers with different shapes (square, round, and E-type, i.e., with an extension on the pressure surface side) and found that E-type tip provided improved performance. The concept of partial shrouded rotor in a small high-speed high-pressure ratio centrifugal compressor was computationally investigated by Tang et al [5]. They found that the leakage flow was reduced in the partially shrouded rotor.…”
Section: Introductionmentioning
confidence: 99%
“…With more advanced manufacturing methods, such as 3D printing, the implementation of splitter blades has become an option for closed impellers. Other impeller range-extension concepts that could be realized through direct metal laser sintering (DMLS) are partially shrouded impellers [14].…”
Section: Range Extension Concept Overviewmentioning
confidence: 99%
“…Tang et al, [6] studied numerically a 3D impeller and vaneless diffuser of a small centrifugal compressor. The influence of impeller tip clearance on the flow field of the impeller was investigated.…”
Section: Previous Workmentioning
confidence: 99%